2003
DOI: 10.1002/bjs.4011
|View full text |Cite
|
Sign up to set email alerts
|

Impact of surgical procedure for gastric cancer on quality of life

Abstract: Background:The aim was to assess quality of life in a group of patients who had a curative resection for gastric cancer. Methods:The European Organization for Research and Treatment of Cancer QLQ-C30 questionnaire with a gastric cancer-specific module was used in patients who had undergone R0 gastrectomy between 1992 and 1999, and who had no disease at the last check-up. A response was obtained from 54 patients, 36 men and 18 women, of mean age 67 years. Of these, 24 patients had total gastrectomy and 26 D2 ly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
32
1
6

Year Published

2003
2003
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(41 citation statements)
references
References 11 publications
2
32
1
6
Order By: Relevance
“…There have been studies comparing the QoL of gastric cancer patients after distal subtotal gastrectomy and total gastrectomy [18][19][20]. In the early postoperative period, patients who underwent distal subtotal gastrectomy experienced better QoL than patients who underwent total gastrectomy, but the QoL benefits of distal subtotal gastrectomy were lost as time elapsed.…”
Section: Discussionmentioning
confidence: 99%
“…There have been studies comparing the QoL of gastric cancer patients after distal subtotal gastrectomy and total gastrectomy [18][19][20]. In the early postoperative period, patients who underwent distal subtotal gastrectomy experienced better QoL than patients who underwent total gastrectomy, but the QoL benefits of distal subtotal gastrectomy were lost as time elapsed.…”
Section: Discussionmentioning
confidence: 99%
“…Jentschura et al [9] and Gockel et al [13] found that patients who underwent subtotal gastrectomy displayed better physical functions, while emotional status and social activities did not differ significantly. On the contrary, Diaz De Liano et al [21] found that the QoL in patients undergoing curative surgery for gastric cancer, regardless of age, was not significantly influenced by type of gastrectomy or whether lymphadenectomy was performed. Thybusch-Bernhardt et al [22] found that the global health status was not negatively influenced by D2 lymphadenectomy and extended gastrectomy, rather, patients with splenectomy were evidently more affected.…”
Section: Discussionmentioning
confidence: 99%
“…This should depend on the size, type and location of the tumour. The QoL in TG patients is worse than those when SG is used [10,11].…”
Section: The Extent Of Resectionmentioning
confidence: 84%